A Comparative Study of Chamling and English Indefinite Pronouns - Rai, Krishna Bahadur (DMC Journal, 2025)
The Chamling and English languages originate from two language families: Sino-Tibetan and Indo-European, respectively. As a result, their systems of indefinite pronouns differ significantly. Additionally, Chamling-speaking children find it challenging to learn English indefinite pronouns. Therefore, this study aims to examine the indefinite pronoun systems of these languages and compare and contrast them to identify similarities and differences. This helps to reduce the interference of Chamling's indefinite pronouns in learning English indefinite pronouns for children who use Chamling as their first language. The study employed a descriptive linguistic approach. Data on Chamling was collected through unstructured interviews with native speakers in Bamrang, Diktel, and Nerpa during field visits. In English, indefinite pronouns are categorised based on their syntactic and morphological features, including compound pronouns and "Of construction" pronouns. Moreover, compound pronouns are further subdivided into universal, assertive, non-assertive, negative, and quantitative categories. English indefinite pronouns also include the “some”, “any”, and “no” series. In contrast, quantitative indefinite pronouns are not part of a series, whereas Chamling indefinite pronouns are classified into two groups: those derived from interrogative forms and non-personal pronouns that include the suffix . The other category comprises indefinite pronouns formed by attaching the suffix to the first group of Chamling indefinite pronouns.